1988
DOI: 10.1159/000212946
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aging on Collateral Circulation via Pial Anastomoses in Cats

Abstract: The effect of aging on collateral circulation via pial anastomoses after middle cerebral artery occlusion was investigated in young and aged cats. The reduction of blood flow and electroencephalography power were greater and collateral vessel resistance was higher in the aged group than the young group. Electroencephalography power after the occlusion was correlated with collateral resistance and blood flow in the two groups. These results suggest that collateral function deteriorates with aging and the high v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…However, collateral metrics were not obtained, and measures of highly localized velocity may not correlate with overall collateral conductance. Compared with young cats, aged cats experienced greater reductions in cerebral blood flow and encephalographic disturbances after MCAO, in association with increased collateral resistance (Yamaguchi et al, 1988).…”
Section: Discussionmentioning
confidence: 89%
“…However, collateral metrics were not obtained, and measures of highly localized velocity may not correlate with overall collateral conductance. Compared with young cats, aged cats experienced greater reductions in cerebral blood flow and encephalographic disturbances after MCAO, in association with increased collateral resistance (Yamaguchi et al, 1988).…”
Section: Discussionmentioning
confidence: 89%
“…From animal experiments, it was determined that a number of factors influence the functionality of LMA, such as variability, 158,159 vascular dynamics, 160 age of the animal, 161 size, 162,163 ischemic edema, 164 and type of experimental occlusion. 165 At the same time, it was found that LMA have an important role in the existence and outcome of the penumbra.…”
Section: Results Of Animal Studiesmentioning
confidence: 99%
“…Others have reported fewer collaterals in the cerebral circulation of aged rats and cats. 22,23 In patients with acute myocardial infarction or stable coronary artery disease, the presence of Rentrop-defined coronary collaterals is inversely related to age. 33,34 However, whether this results from a decline in native collateral extent before or from reduced collateral remodeling after onset of coronary atherosclerosis, and thus less detection, cannot be distinguished in such studies.…”
Section: Discussionmentioning
confidence: 99%